Study on the association between genetic variation of gag gene and HLA restricted CTL response in HIV-1 B' infected Chinese people - Zhang, Hui; Han, Xiao-xu; Dai, Di; Zhao, Bin; An, Ming-hui; Shang, Hong (Zhong hua yi xue za zhi, 2013)
To identify the genetic variation of Gag gene in HIV-1 B' subtype infected Chinese people and to evaluate the association between the positive selection sites and HLA restricted CTL response. We downloaded all HIV-1 B' subtype gag gene sampled from China from the LANL HIV database. The sequences were grouped by years of collection and the mean intra-subtype diversity and divergence were examined by MEGA 5.0 software. The sites under positive selection were estimated by using Hyphy software. Then analyzed the association between positively selected sites and HLA restricted CTL epitopes. A set of 122 B' subtype HIV-1 gag sequences were collected from Henan, Hubei, Liaoning and Yunnan provinces, grouped by sampling year as < 2001, 2001 - 2003, 2004 - 2006 and 2007 - 2010. The mean intra-subtype diversity and divergence increased over time (r(1) = 0.497, P1 < 0.001; r(2) = 0.593, P2 < 0.001). This analysis revealed 34 positively selected sites and 97.1% of these sites were located within 47 known CTL epitopes. Th